Pengaruh Kemampuan Membaca Pemahaman dan Pemahaman Kalimat Terhadap Kemampuan Memecahkan Soal Cerita Matematika - Ardianik, Ardianik; Utami, Sri; Kusmiyati (Universitas Dr. Soetomo, 2024)
Reading and comprehending a text has long been considered quite challenging. This may occur because individuals are often reluctant to take the time to read and then understand the content. However, without performing both tasks, one cannot fully grasp or comprehend the material presented. This issue becomes even more pronounced in mathematical word problems. Everyone must still learn mathematics because it serves as a tool for solving everyday problems, much like language, reading, and writing. Mathematics is not just about writing; it involves understanding concepts by first reading and comprehending them. This study aims to examine and prove: (1) The influence of reading comprehension ability on the ability to solve mathematical word problems; (2) The influence of sentence comprehension ability on the ability to solve mathematical word problems; (3) The influence of both reading comprehension and sentence comprehension on the ability to solve mathematical word problems. This quantitative research uses an ex-post facto approach, with data collected through tests, including reading comprehension tests, sentence comprehension tests, and mathematical word problem-solving tests. The data analysis method used is multiple linear regression, with assumptions already fulfilled. The results of the study show: (1) There is a highly significant influence of reading comprehension ability on the ability to solve mathematical word problems; (2) There is a highly significant influence of sentence comprehension ability on the ability to solve mathematical word problems; (3) There is a highly significant influence of both reading comprehension and sentence comprehension on the ability to solve mathematical word problems among 11th-grade students in the TKJ (Computer and Network Engineering) and Multimedia departments at UNITOMO Vocational School, Surabaya.